ISOLASI PROTOPLAS TANAMAN KACANG HIJAU (Vigna radiata (L.) Wilczek) SECARA ENZIMATIK DENGAN KOMPOSISI ENZIM BERBEDA - Mohamad Nurzaman; Tia Setiawati (Universitas Padjadjaran, 2002)
The effects of different enzyme compositions and age of explants on protoplasts isolation of mungbean (Vigna radiata (L) Wilczek) had been carried out. Protoplasts were isolated from the first leaves of 5, 6, 7, and 8 days old of mungbean seedling, which were incubated in 5 types enzyme composition for 4 hours. The results showed that the yield of protoplasts more than 106 protoplas/g leaf for all combinations. The highest yield of protoplasts (3,4 x 107 protoplasts/g leaf) were obtained from 7 days old seedling using a combination of 4% Meicelase P-1, 1% Macerozyme R-10 and 0.5 M mannitol. From these results, it can be concluded that the type of enzyme compositions and age of explants influent the yield of protoplasts isolation